EXAMINING PUBLIC SATISFACTION OF LOMBOK TENGAH REGENCY CIVIL REGISTRY SERVICE OFFICE ADMINISTRATIVE SERVICE BASED ON GOVERNMENT SYSTEM - Ida Surya (Jurnal Ilmiah Wahana Bhakti Praja, 2020)
ABSTRACT. Public service is something that needed by the public. So in this regard, the government as an official public body has the duty and responsibility to provide the best service to the public itself. But the efforts made as a public service provider do and work, certainly not able to provide satisfaction to the public itself. Satisfaction with a service is one of the rights that obtained by someone. "In accordance with the Universal Declaration of Human Rights, ideals about free human beings, who enjoy civil and political freedom, and freedom from fear and poverty can only be achieved, if conditions are created where everyone can enjoy civil rights and its politics and economic, social and cultural rights”. To obtain input/information about public satisfaction in the field of population administration and civil registration services in Lombok Tengah Regency, researchers tried to conduct research, with survey methods, in order to obtain input from the public how about public services performed by public service providers in Lombok Tengah District, in the area of ​​population administration and civil registration services.